Heart–brain interaction in cardiogenic dementia: pathophysiology and therapeutic potential - Liu, Jiaxu; Xiao, Guangxu; Liang, Yujuan; He, Shuang; Lyu, Ming; Zhu, Yan (Frontiers in Cardiovascular Medicine, 2024)
Diagnosis and treatment of patients with cardiovascular and neurologic diseases primarily focus on the heart and brain, respectively. An increasing number of preclinical and clinical studies have confirmed a causal relationship between heart and brain diseases. Cardiogenic dementia is a cognitive impairment caused by heart dysfunction and has received increasing research attention. The prevention and treatment of cardiogenic dementia are essential to improve the quality of life, particularly in the elderly and aging population. This study describes the changes in cognitive function associated with coronary artery disease, myocardial infarction, heart failure, atrial fibrillation and heart valve disease. An updated understanding of the two known pathogenic mechanisms of cardiogenic dementia is presented and discussed. One is a cascade of events caused by cerebral hypoperfusion due to long-term reduction of cardiac output after heart disease, and the other is cognitive impairment regardless of the changes in cerebral blood flow after cardiac injury. Furthermore, potential medications for the prevention and treatment of cardiogenic dementia are reviewed, with particular attention to multicomponent herbal medicines.